Multi-body Dynamics Simulation of Timing Belt Drive System for Automotive Engine based on RecurDyn - Zengming Feng; Jinxing Yang (Jixie chuandong)
Based on the multi-body dynamics software RecurDyn, combined with the layout design parameters of a gasoline engine timing belt drive system, the multi-body dynamics simulation model of the timing belt drive system is established. Through theoretical and simulation calculation, the causes of static contact force error between pulley and timing belt are analyzed, the variation law of tension and transmission error of timing belt is studied, and the response characteristics of meshing frequency and excitation frequency are analyzed through frequency domain analysis. The results show that the multi-body dynamics simulation technology based on RecurDyn can provide an effective and reliable research method for the dynamic characteristics analysis and performance evaluation of timing belt drive system.